cis -Decalinoyltetramic Acid Derivatives from the Palm Fungus Leptosporella arengae TBRC-BCC32590 - Chakapong Intaraudom; Nantiya Bunbamrung; Aibrohim Dramae; Sutichai Nithithanasilp; Nattawut Boonyuen; Chitti Thawai; Khomsan Supong; Patchanee Auncharoen; Pranee Rachtawee; Pattama Pittayakhajonwut (Journal of Natural Products, 2025)
(MIC 6.25 - > 50.0 μg/mL). Cytotoxicity against both cancerous (MCF-7 and NCI-H187) and noncancerous (Vero) was also reported.
Keywords: Microbial Natural Products and Biosynthesis; Microbial Metabolism and Applications; Bioactive Natural Diterpenoids Research